Research on coupling relationship between ECG and PW signal in the cardiovascular system - Jiang, Fangfang; Song, Shaoxiu; Cheng, Jiabin; He, Siliang; Yang, Xiao (Technology and health care, 2015)
Cardiovascular disease (CVD) has become the main cause of morbidity and mortality world-wide. In order to obtain the potential function of cardiovascular system information further, the parameters of the coupling relationship between Electrocardiogram (ECG) signal and Pulse Wave (PW) signal are proposed. In this paper, we detected the peaks of ECG and PW signal synchronously from the Fantasia database using Empirical Mode Decomposition (EMD) algorithm, and analyzed the interval between different age groups in the same domain, then calculating the Euclidean distance to characterize the coupling relationship. Via the experimental results of 20 subjects, the parameters of the old group were always larger than the young group. Thus the synchronization and consistency for PW following the ECG are weaker than the young group, which is in keeping with the clinical rule. The conclusion is that there is a certain representation for the cardiovascular system with the coupling relationship parameter proposed.